Hepatosplenic T-cell lymphoma, αβ type, presenting in an elderly patient status post indolent B-cell lymphoma treatment: report of a case and review of the literature - Rodolfo Garza-Morales; Isabela Wen-Chi Chang; Allison Rosenthal; Jiehao Zhou (Human Pathology Reports)
Hepatosplenic T-cell lymphoma (HSTL) is a rare and aggressive mature T-cell lymphoma characterized by hepatosplenic involvement. It usually occurs de novo in adolescents and young adults (AYA) and has been most commonly reported in the setting of immunosuppression. Most cases present with proliferation of cytotoxic T-cells of TCRγδ type with a unique gene mutation profile. Due to rarity of this disease, there is no standard of care treatment, and outcomes are usually poor in the absence of stem cell transplant. In this case, we report an unusual presentation of HSTL of TCRαβ type in an elderly patient status post treatment of an indolent B-cell lymphoma.